Perdagangan Produk Imitasi Perspektif UU No. 15 Tahun 2001 Dan Hadis Riwayat Ahmad - Sabili Casba Ar-Rusd; Tajul Arifin (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The research is aimed at finding, understanding, and analyzing the juridic components that cause counterfeit goods to circulate to the public. In addition, the study also investigates how governments and brand owners can prevent counterfeits. This study uses a normative or normative jurisprudential approach; or in other words, this study is about favorable legal norms as the topic of legal research as well as the Hadith perspective of Ahmad's history. The existence of free trade produces an unlimited trade market, which produces a wider distribution of goods and services in society. Brands play an important role inining healthy competition as trade in products and services has grown. The owner’s as the only proprietor of the goods is to prevent the violation of the trademark. For example, the common and increasing public violation is counterfeiting of goods, which affects the increased public demand for counterfeit goods. In addition, the economic and cultural factors of communities also contribute to the circulation of counterfeit goods in communities. The study’s findings demonstrate that brand owners and the government have not fully protected their right to prevent the circulation of counterfeit goods. Until now, only the original brand owners have been active in preventing the spread of the counterfeit